2020
DOI: 10.1515/ijfe-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maltodextrin and arabic gum ratio on physicochemical characteristic of spray dried propolis microcapsules

Abstract: Propolis has known as an aromatic resin which possesses several health beneficial properties such as antimicrobial and antioxidant due to bioactive and its complex composition. Propolis has been utilized in the form of extract however the application in food is limited due to its insolubility in water and undesirable sensory characteristics. Propolis encapsulation by spray drying with maltodextrin with or without gum Arabic could reduce the undesirable sensory characteristic, protect bioactive compounds, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Moreover, there is a peak concentration of Arabic gum, which is the most effective concentration to maintain the antioxidant activity of microencapsulated extracts. This result is in line with the report by Sukri et al [6], which encapsulated phenolic extract from propolis with different concentrations of Arabic gum and showed a peak of the most effective Arabic gum concentration to preserve the phenolic content in microcapsules.…”
Section: Antioxidant Activity Of Microencapsulated C Ternatea Extractsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, there is a peak concentration of Arabic gum, which is the most effective concentration to maintain the antioxidant activity of microencapsulated extracts. This result is in line with the report by Sukri et al [6], which encapsulated phenolic extract from propolis with different concentrations of Arabic gum and showed a peak of the most effective Arabic gum concentration to preserve the phenolic content in microcapsules.…”
Section: Antioxidant Activity Of Microencapsulated C Ternatea Extractsupporting
confidence: 93%
“…Various types and combinations of coating agents used to encapsulate anthocyanin have been studied and reported in the literature. Maltodextrin and Arabic gum are the most common materials used for microencapsulation [6], as well as their combination together or with other coating agent materials such as gelatin, carrageenan, and cyclodextrin. Maltodextrin is commonly used as a coating agent due to its high solubility in water and high retention of bioactive compounds [84,85].…”
Section: Coating Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased level of {\text{X}}_{2} in turn, increased the hygroscopicity of encapsulated product can be associated with easier polar interaction between its hydrogen chain and water due to different polarity and the highly branched structure of the gum arabic. A similar pattern of increase in hygroscopicity from 9.18-10.66% was observed with the increase of gum arabic from 0-2% in wall material along with maltodextrin during spray dried encapsulation of propolis extract (Sukri et al, 2021). Results reported for microwave-assisted encapsulated anthocyanins from Ipomoea batatas showed that the product with only maltodextrin, only gum arabic and combination of both as wall material was found to have low…”
Section: Effect Of Process Parameters On Hygroscopicitysupporting
confidence: 70%